Assessment of Fiber Chromatic Dispersion Based on Elimination of Second-Order Harmonics in Optical OFDM Single Sideband Modulation Using Mach Zehnder Modulator. Issue 4 (3rd July 2016) - Patel, Dhananjay; Singh, Vinay Kumar; Dalal, U. D.
ABSTRACT: This work addresses the analytical and numerical investigations of the transmission performance of an optical Single Sideband (SSB) modulation technique generated by a Mach Zehnder Modulator (MZM) with a 90° and 120° hybrid coupler. It takes into account the problem of chromatic dispersion in single mode fibers in Passive Optical Networks (PON), which severely degrades the performance of the system. Considering the transmission length of the fiber, the SSB modulation generated by maintaining a phase shift of π /2 between the two electrodes of the MZM provides better receiver sensitivity. However, the power of higher-order harmonics generated due to the nonlinearity of the MZM is directly proportional to the modulation index, making the SSB look like a quasi-double sideband (DSB) and causing power fading due to chromatic dispersion. To eliminate one of the second-order harmonics, the SSB signal based on an MZM with a 120° hybrid coupler is simulated. An analytical model of conventional SSB using 90° and 120° hybrid couplers is established. The latter suppresses unwanted (upper/lower) first-order and second-order (lower/upper) sidebands. For the analysis, a varying quadrature amplitude modulation (QAM) Orthogonal Frequency Division Multiplexing (OFDM) signal with a data rate of 5 Gb/s is upconverted using both of the SSB techniques and is transmitted over a distance of 75 km in Single Mode Fiber (SMF). The simulation results show that the SSB with 120° hybrid coupler proves to be more immune to chromatic dispersion as compared to the conventional SSB technique. This is in tandem with the theoretical analysis presented in the article.